Clean development mechanism in Iran: does it need a revival?. (2016) - Alizadeh, Reza; Majidpour, Mehdi; Maknoon, Reza; Kaleibari, Saeed Shafiei
This paper aimed to study clean development mechanism (CDM) projects in Iran. Greenhouse gas mitigation strategies are generally considered costly with world leaders often engaging in debate concerning the costs of mitigation and the distribution of these costs between different countries. CDM projects are useful tools to reduce these costs. Kyoto Protocol includes three mechanisms, namely: emission trading, joint implementation and CDM. CDM is the only mechanism of the Kyoto Protocol and United Nations Framework Convention on Climate Change (UNFCCC) in which developing countries can participate. Comprehensive interviews with experts from Iranian oil and energy ministries and Department of Environment (DOE) resulted in detecting the missed opportunities for CDM in Iran. Lack of long term planning for the Kyoto Protocol, limitation of technology and finance, lack of regulation and functionality of a financial system and international sanctions are the most significant obstacles for implementation of CDM projects in Iran. At the end, a comprehensive analysis for utilising CDM to greenhouse gas reduction and climate change mitigation is presented.